Response of tef (Eragrostis tef (Zucc.) Trotter) yield to nutrient management under rainy and irrigation production systems in northwestern Amhara, Ethiopia - Zerfu Bazie; Tadele Amare; Erkihun Alemu; Bitewulign Kerebh; Abere Tenagn; Abrham Awoke; Zmie Ambaw; Beamlaku Alemayehu; Anteneh Abewa; Ataklte Abebe; Tesfaye Feyisa; Birhanu Agumas (PLoS ONE, 2025)
Crops respond differently to soil nutrients because of climate, soil, and management. This study aimed to determine the most important nutrients for tef production. The experiment was conducted over two production seasons. All (NPKSZnB), All-B, All-Zn, All-S, All-K, All-P, All-N, RNP, RNP+Sx1, and no fertilizer treatments were applied. The pre-planning soil status of the study sites, available P concentrations during the rainy season are between 5.1 and 8.9 mg kg-1, however, 21.4 mg kg-1 of available P is observed during irrigation. In rain-fed production systems, the mean soil N concentrations are 0.12% in nitisols and 0.15% in vertosols, whereas in irrigation production systems, it is 0.14% in nitiosols. The grain yield significantly (p ≤ 0.01) varied with the omission of nutrients during the production season. However, there was no significant (p<0.05) decrease in yield due to the omission of KSZnB nutrients. The lowest mean grain yields of 342 kg ha-1 (nitisols) and 491 kg ha-1 (vertosols) were obtained from the no fertilizer treatment. Nitrogen omission decreased yields by 49 and 65% in nitisols and vertosols under the rainy season, respectively, whereas a 19% yield decrease was also observed in the irrigation season. A 10% yield decrease was observed from the P omitted treatment in the rainy season. Thus, N is the primary limiting nutrient to yield in both production seasons, while P is also a yield-limiting nutrient in nitisols. Thus, the government should import the right kind of fertilizer to boost crop productivity in Ethiopia. The required plant nutrients should be periodically monitored in farming systems.